Peningkatan Argumentasi Ilmiah dan Hasil Belajar Siswa SMA pada Hukum Dasar Kimia melalui Learning Cycle 5E: Penelitian - Ismiatul Zaroh; Ridwan Joharmawan; Brian Anggriawan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study examines the effectiveness of the 5E Learning Cycle model in improving students' learning outcomes and scientific argumentation skills, including claims, evidence, and reasoning. The research method used was descriptive quantitative with 26 students of grade X-2 participating. Data were collected through pretests and posttests of learning outcomes and argumentation assessments during two learning cycles. The results showed that 73.1% of students experienced an increase in argument quality, 11.5% remained the same, and 15.4% experienced a decrease. The N-Gain value for cognitive learning outcomes was 0.56, which is included in the moderate category. Interviews showed that students with improved argumentation felt more engaged and challenged in learning, while students with decreased argument quality experienced difficulties in articulating reasoning and integrating evidence. These findings indicate that the 5E LC model is effective in improving students' learning outcomes and scientific argumentation skills, although additional support in the form of explicit argument scaffolding is needed to help all students develop these abilities optimally.